The criteria of Chinese and South Koreans’ mate selection: A comparative study of long-term and short-term mate selection preferences in the cross-cultural perspective - Yunhang Lu (Heliyon, 2023)
Sexual selection has become an important research topic in behavioral ecology, human behavior, and evolution. The study of mate selection preferences across cultures and countries has gradually received increasing attention. The present study was aimed to reveal the differences of long-term and short-term mate selection preferences between young people in Chinese and South Korean. An questionnaire survey method was followed to obtain the aim of the study, and a total of 273 Chinese (M = 22.07, SD = 1.75) and 181 Koreans (M = 21.75, SD = 2.05) unmarried university students were chosen to participate the study. We summarized the important core factors of individual mate preferences and revealed the long-term and short-term mate preferences of young men and women in both countries through quantitative analysis. The results indicated that education played a crucial role in the long-term mate selection for both Chinese males and females. Contrastingly, Koreans valued friendliness and easygoingness in long-term mate value and liveliness in short-term mate value. There were differences found in mate preference by gender between Chinese and Koreans, influenced by cross-cultural factors. These findings strongly supported cultural differences in mate selection and provided practical suggestions for future cross-cultural mate selection research.